Original paperLAND WHERE YOU LOOK? – FUNCTIONAL RELATIONSHIPS BETWEEN GAZE AND MOVEMENT BEHAVIOUR IN A BACKWARD SALTO - Heinen, T.; Jeraj, D.; Vinken, P.M.; Velentzas, K. (Biology of Sport, 2012)
In most everyday actions the eyes look towards objects and locations they are engaged with in a specific task and this information is used to guide the corresponding action. The question is, however, whether this strategy also holds for skills incorporating a whole-body rotation in sport. Therefore, the goal of this study was to investigate relationships between gaze behaviour and movement behaviour in a complex gymnastics skill, namely the backward salto performed as a dismount on the uneven bars. Thirteen expert gymnasts were instructed to fixate a light spot on the landing mat during the downswing phase when performing a backward salto as dismount. The location of the light spot was varied systematically with regard to each gymnast’s individual landing distance. Time-discrete kinematic parameters of the swing motion and the dismount were measured. It was expected that fixating the gaze towards different locations of the light spot on the landing mat would directly affect the landing location. We had, however, no specific predictions on the effects of manipulating gaze direction on the remaining kinematic parameters. The hip angle at the top of the backswing, the duration of the downswing phase, the hip angle prior to kick-through, and the landing distance varied clearly as a function of the location of the light spot. It is concluded that fixating the gaze towards the landing mat serves the function to execute the skill in a way to land on a particular location.